Kajian Konseptual Tentang Pemilihan Umat Allah Dalam Kitab Torah - Deklay Nainggolan (Peneliti.net, 2022)
Conceptual Review of God's Elections in Torah. Rejection of Israel as God's chosen nation, and justification of the Gentiles by faith is in the sovereignty of God. Paul explains God's act toward His chosen people in the past, in which Israel is distancing itself from God's mercy and neglecting its opportunity. In the present, Israel as a nation rejects the Messiah. In the future, Israel as a nation, will receive the Messiah and enjoy the promised blessings with the oath promise in the Old Testament. The key pressure of this context is that God's sovereignty is expressed in a vacuum, not a mere power. The choice of God's sovereignty is not based on an early knowledge of the choices and actions that humans will take in the future. However, God chooses to bless the unworthy through his faith (not on the basis of his achievement). God knows everything but He chooses to limit His choice in mercy and in promise. The human response must exist, but it follows and ultimately affirms the life-changing choice of God. On the sovereignty of God who has chosen who is chosen it can force us to draw the conclusion that God is 'unfair'. Paul has said that God's election is not bound to a lineage, that God is free to choose some of Abraham's offspring and reject some of the others.